Compared to Intermittant Claudication Critical Limb Ischemia Is Associated with Elevated Levels of Cytokines - Jalkanen J; Maksimow M; Hollmen M; Jalkanen S; Hakovirta H (PUBLIC LIBRARY SCIENCE, 2022)
Critical limb ischemia (CLI) is the advanced stage of peripheral artery disease (PAD) and associated with an extremely poor clinical outcome. In order to understand the possible role of circulating cytokines and poor outcome associated with CLI we compared the circulating cytokine profile of patients with CLI against patients with intermittent claudication (IC). The levels of 48 circulating cytokines were examined in 226 consecutive patients with peripheral artery disease (PAD) admitted for elective, non-urgent, invasive treatment of IC or CLI. The PAD patient cohort was evenly distributed between subjects with IC (46.5%) and CLI (53.5%). As accustomed in PAD, CLI was associated with higher age, chronic kidney disease and diabetes when compared to IC (P < 0.01 for all). In multivariable linear regression modeling taking into account the baseline differences between IC and CLI groups CLI was independently associated with elevated levels of a large number of cytokines: IL-1 beta, IL-1ra, IL-2R alpha, IL-4, IL-6, IL-10, IFN-gamma, GM-CSF, G-CSF (P < 0.01 for all), and IL-2, IL-7, IL-12, IL-13, IL-17, bFGF, VEGF, SCGF-beta (P < 0.05 for all). The current findings indicate that CLI is associated with a circulating cytokine profile, which resembles serious medical conditions such as severe pancreatitis, sepsis, or even cancer. Compared to IC, CLI is a systemic inflammatory condition, which may explain the extremely poor outcome associated with it.